General and specific combinatorial aptitude of low-inbreeding yellow maize varietal hybrids - López López, Consuelo; Tadeo-Robledo, Margarita; García-Zavala, J Jesús; Espinosa-Calderón, Alejandro; Mejía-Contreras, J Apolinar (Revista Mexicana de Ciencias Agrícolas, 2021)
The production of yellow maize (Zea mays L.) in Mexico is in deficit and its demand increases every year. In this paper, the effects of general and specific combinatorial aptitude, maternal and reciprocal effects for yield variables and their components of five varieties of yellow maize with low level of inbreeding and their diallel crosses were estimated. All genotypes were evaluated in a randomized complete block experimental design with three repetitions per environment, during the spring-summer cycle from 2017 to 2019. Genetic analysis was performed using Griffing’s method I. The results indicated that the variety IA324 due to its high yield would have a high contribution in the expression of the yield of its progeny and could be included in a maize genetic improvement program. The direct and reciprocal crosses with higher specific combinatorial aptitude (ACE) for yield were HVAA-10 x IA324 and IA324 x HVAA-9, respectively. It was found that the use of progenitors of contrasting general combinatorial aptitude (ACG) allowed the favorable expression of their progeny. The yellow grain varieties of this work with high ACG effects can be used to develop synthetic varieties or continue advancing more selection cycles, considering that the lines with high ACG detected in early tests retain their additive values in advanced generations, while crosses with high ACE can be used for hybridization.
Keywords: Zea mays L.; general combinatorial aptitude; specific combinatorial aptitude; varietal hybrids